A Rare Case of a Pure Testicular Seminoma Presenting 7 Years after a Pineal Germinoma - Usman Najeeb Bhatty; Mohammed Hayat Ashrafi; Caroline Mary Nicholson; Ahsanul Haq (Case Reports in Urology)
Pure testicular seminomas occurring in patients with previous intracranial germ cell tumours are extremely rare. We present such a case. A 37-year-old gentleman presented to urology after previously being treated for a pineal germinoma with steroids and radiotherapy. On routine followup, he described symptoms of a testicular seminoma. This was managed surgically with radical orchidectomy. We discuss the possible causes of such an association with a review of the literature.